ADC*E The Annual Of Annuals 2014 - Mouzouropoulos, Theseas (My University, 2014)
The Semiotics and Visual Communication Lab (www.svclab.com) was commissioned by the Water Board of Limassol to visually communicate the significant decrease of rain falls during the year 2013 and the problem of water leaks at Lemesos district in Cyprus. We conducted a research and analysis of the data regarding the water flow and storage in dams as well as we analysed the data, cause and prevention of water leaks. Finally we designed a series of posters based on a combination of data visualization and minimal infographics in order to communicate the problems aforementioned. The design process was successfully completed and 100,000 posters were included within the consumer's water bills on separate periods during 2013.
Keywords: Graphic Design; information design